Clays and Clay Minerals, Vol. 56, No. 1, 82–89, 2008. - Letaief, Sadok; Detellier, Christian (The Clay Minerals Society, 2008)
Ionic liquids intercalated in kaolinite constitute a novel class of nanostructured material. Kaolinite-pyrrolidinium halide intercalates have been prepared successfully by reacting the pyrrolidinium salts with kaolinite which was preintercalated with dimethyl sulfoxide (DMSO) using the melt condition under N2. X-ray diffraction, 13C magic angle spinning nuclear magnetic resonance, differential thermal analysis (DTA)-thermal gravimetric analysis, and Fourier transform infrared spectroscopy confirm the displacement of DMSO during the intercalation process. Based on results from the various characterization techniques, a structural model is proposed in which one mole of the pyrrolidinium salt covers two or three structural units of kaolinite, depending on the structure and size of the salt. The thermal stability was improved remarkably after intercalation of the pyrrolidinium salts, compared to the pre-intercalate. The DTA-TGA data show that the largest number of organic units released and decomposed, occurs under N2 flow, at temperatures ranging from 260 to 340ºC, depending on the nature of the intercalated organic salts.
Ionic Liquids-kaolinite Nanostructured Materials. Intercalation Of Pyrrolidinium Salts
Clays and Clay Minerals, Vol. 56, No. 1, 82–89, 2008. Ionic Liquids-kaolinite Nanostructured Materials. Intercalation Of Pyrrolidinium Salts. Sadok Letaief; Christian Detellier. DOI: 10.1346/CCMN.2008.0560107. Copyright © 2008, The Clay Minerals Society.
Keywords: Periodicals; Geology; 13C CP/MAS NMR; FTIR; Intercalation; Ionic Liquids; Kaolinite; Nanohybrid Materials; Nanostructured Materials; Pyrrolidinium; 29Si CP/MAS NMR; TGA; XRD